Yamanaka Factors in the Budding Tunicate Botryllus schlosseri Show a Shared Spatio-Temporal Expression Pattern in Chordates - Vanni, Virginia; Salonna, Marika; Gasparini, Fabio; Martini, Margherita; Anselmi, Chiara; Gissi, Carmela; Manni, Lucia (Frontiers in Cell and Developmental Biology, 2022)
In vertebrates, the four transcription factors Sox2, c-Myc, Pou5f1 and Klf4 are involved in the differentiation of several tissues during vertebrate embryogenesis; moreover, they are normally co-expressed in embryonic stem cells and play roles in pluripotency, self-renewal, and maintenance of the undifferentiated state in adult cells. The in vitro forced co-expression of these factors, named Yamanaka factors (YFs), induces pluripotency in human or mouse fibroblasts. Botryllus schlosseri is a colonial tunicate undergoing continuous stem cell-mediated asexual development, providing a valuable model system for the study of pluripotency in the closest living relatives of vertebrates. In this study, we identified B. schlosseri orthologs of human Sox2 and c-Myc genes, as well as the closest homologs of the vertebrate-specific Pou5f1 gene, through an in-depth evolutionary analysis of the YF gene families in tunicates and other deuterostomes. Then, we studied the expression of these genes during the asexual cycle of B. schlosseri using in situ hybridization in order to investigate their possible involvement in tissue differentiation and in pluripotency maintenance. Our results show a shared spatio-temporal expression pattern consistent with the reported functions of these genes in invertebrate and vertebrate embryogenesis. Moreover, Myc, SoxB1 and Pou3 were expressed in candidate stem cells residing in their niches, while Pou2 was found expressed exclusively in the immature previtellogenic oocytes, both in gonads and circulating in the colonial vascular system. Our data suggest that Myc, SoxB1 and Pou3 may be individually involved in the differentiation of the same territories seen in other chordates, and that, together, they may play a role in stemness even in this colonial ascidian.